Pharmacokinetic Profile of Bioanalytical Method Development and Validation of Clarithromycin from Human Plasma by Using Liquid Chromatography Tandem Mass Spectrometer - Jayavel, Jayaprakash; Duraisamy, Umamaheshwari; Mohan, Kumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim: To develop and validate a sensitive and specific bioanalytical method for the quantification of clarithromycin in human plasma using Liquid Chromatography-tandem Mass Spectrometry (LC-MS/MS). Additionally, to characterize the pharmacokinetic profile of clarithromycin, including its Absorption, Distribution, Metabolism, and Excretion (ADME) in humans. This study aims to support the clinical application and therapeutic monitoring of clarithromycin. Background: Of this study was to develop and validate a bio-analytical method for the quantification of clarithromycin in human plasma utilizing Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS). Clarithromycin, a widely used macrolide antibiotic, requires accurate and sensitive measurement in biological matrices to ensure therapeutic efficacy and monitor Pharmacokinetic (PK) profiles. The test preparation is the product being evaluated and the reference preparation is the preparation which is used to compare the test product. Pharmacokinetic or Indirect method There exist a linear relation between the drug level in the biological fluid and therapeutic response; therefore, these methods are also known as indirect methods. Solid Phase Extraction SPE is a technique to clean, separate and concentrate analyte prior to analysis. Involves passing sample through a sorbent bed that preferentially retains the analyte under the right conditions. PPT Precipitation is another method of concentration that is used extensively for biopolymer such as protein, polypeptide, etc. by increasing the concentration of a protein solution some protein can be precipitated. Materials and Methods: Human plasma samples were analyzed using a developed and validated LC-MS/MS method to quantify clarithromycin. The method underwent rigorous validation for accuracy, precision, linearity, and stability, followed by pharmacokinetic analysis to assess clarithromycin’s ADME profile. Conclusion: Utilizing advanced analytical techniques such as HPLC coupled with MS, the method exhibits excellent performance characteristics, including high sensitivity, specificity, and reproducibility. he successful implementation of this method underscores its value in both clinical settings and research, contributing to better understanding and management of clarithromycin pharmacokinetics. his method's ability to provide precise and reliable data makes it an essential tool for therapeutic drug monitoring and pharmacokinetic studies of clarithromycin, ultimately contributing to improved patient care and optimized treatment outcomes. And determine the suitable parameters followed by ICH guidelines.
Keywords: Pk; LCMS System; Clarithromycin; Bioavailability; Solid Phase Extraction; Protein; Precipitation